Análise exploratória da influência de alianças estratégicas no capital intelectual de empresas - Carvalho, Rodrigo Malheiros Gonçalves (2005)
This research verified the influence of strategic alliances on the generation of intangible assets in the Brazilian manufacturers. A field research targeted at the senior management of firm covering around 5% of the net sales of this economic segment in Brazil was developed. The aim of the field research was: i) to validate the hypothesis proposed in the theoretical framework that suggested the existence of a relationship between the development of strategic alliances and the development of competitive advantages to the allied firms, through the positive variation of these firms¿ intellectual capital or intangible assets; ii) to capture data for the development of an exploratory analysis of the subjacent characteristics of this relationship. This study is based on theoretical framework that contextualizes the current economic era - the so called information economy - unveils the existing taxonomy of intangible assets and strategic alliances, taking into account their importance to the competitiveness of modern organizations, and presents categorizations for intangibles and alliances, within the business realm. The results of this research showed that the development of strategic alliances is positively correlated to the increase of intangible assets of the companies studied. Furthermore, indications were found that innovation-based alliances are the ones that contribute more intensely to the development of intangible assets of the allies. Lastly, it was perceived that the more different kinds of alliances are developed simultaneously, the smaller the benefits in terms of intellectual capital generation.